Uma nova família de conversores com comutação ZCS na abertura e fechamento das chaves - Dias, Emmanuel Cordeiro (2008)
This work presents a new non-dissipative commutation cell applicable to any traditional DC-DC converters topology. The proposed cell is composed of one main switch and two auxiliary switches operating with zero current turn on and off. Semiconductor as MOSFETs, transistors and IGBTs can be used in the cell, but it needs a more sophisticated control. The use of SCRs requires a more simple control, promoting greater robustness to the cell, although, with the price of working at frequencies far below those likely to be used with the switch above mentioned. Simulations presented the principle of operation of the structure. A prototype using the Buck topology was developed and the experimental results obtained were compared with the results of simulation to demonstrate and validate the research.